2018
DOI: 10.4103/jgid.jgid_55_17
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated protothecosis caused by Prototheca zopfii in a liver transplant recipient

Abstract: Prototheca is a genus of achlorophyllic algae present ubiquitously in the environment. Human infections are rare affecting immunocompromised individuals. We report a case of fatal algaemia caused by Prototheca zopfii in a patient who underwent liver transplant. Tissue diagnosis is mandatory for diagnosing rare entities in seriously ill, immunocompromised individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The overall mortality rate of P. zopfii in this series was 64% (9/14), compared with the reported mortality rates of 50%–75% for disseminated P. wickerhamii . 1,2,13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mortality rate of P. zopfii in this series was 64% (9/14), compared with the reported mortality rates of 50%–75% for disseminated P. wickerhamii . 1,2,13…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rate of P. zopfii in this series was 64% (9/14), compared with the reported mortality rates of 50%-75% for disseminated P. wickerhamii. 1,2,13 The range of 50%-75% in the mortality rate of P. wickerhamii is attributed to inconsistency in the definition of disseminated Prototheca infections in the literature. In an article written by Todd et al, 2 they define disseminated infection as involving at least 2 different organs, whereas others who examined the same case reports consider any infection other than a localized cutaneous or olecranon bursitis as disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…Protothecosis is a rare algal infection with varying clinical presentations in humans and nonhuman vertebrates ( 24 ). In 2017, Todd et al reported that only 211 cases of human protothecosis had been published worldwide up to April 2017 ( 25 ), although these numbers appear to be rising ( 26 , 27 ). Of more significance is Prototheca -associated bovine mastitis, a subtype of mammary gland inflammation with drastic impact on the dairy industry worldwide ( 6 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protothecosis is a rare disease associated with Prototheca, a genus of unicellular algae that is ubiquitous in nature and most prevalent in humid climates and aqueous environments. 1 Prototheca wickerhamii is the Prototheca variant most commonly associated with human disease. The organism is typically introduced into the skin via trauma in contaminated water, with the trauma characteristically not recognized or remembered by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Protothecosis is a rare disease associated with Prototheca , a genus of unicellular algae that is ubiquitous in nature and most prevalent in humid climates and aqueous environments . Prototheca wickerhamii is the Prototheca variant most commonly associated with human disease.…”
Section: Discussionmentioning
confidence: 99%